The willingness to pay for better environment: the case of pineapple cultivation on peat soil in Samarahan, Sarawak - Daud, Adrian; Abdul Rahim, Khalid; Shamsudin, Mad Nasir; Shuib, Ahmad (School of Social Sciences, Universiti Sains Malaysia, 2012)
Pineapple cultivation practiced in Samarahan, Sarawak adopted the traditional method of residue burning (RB). Peat soil, which contains high amount of carbon, released carbon dioxide into the atmosphere when RB is practiced and this method is harmful to the environment as it caused among others air pollution. The air quality deteriorated when there is open burning and this can lead to the haze problem when large scale burning is involved. Zero burning (ZB) is a more sustainable method as it mitigated the release of carbon into the atmosphere and it is a step to achieve a better environment. The villagers and farmers in Samarahan are asked to state their willingness to pay (WTP) for better environment in this study and 206 respondents were interviewed. The average WTP among the respondents was RM4.12. This low value is expected as most of the farmers are low income earners but this should not be seen as giving a low environmental value by the community in this area. Policymakers are sometimes looking at the monetary value/cost per se but this does not necessarily mean a relatively low WTP value justifies the lack of effort to promote good agricultural practices such as ZB.